Anisotropia da variabilidade espacial da emissão de co2 do solo sob cultivo de cana-de-açúcar e eucalipto - Veras, Ludhanna Marinho [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O dióxido de carbono (CO2) é um dos principais gases do efeito estufa adicional, sendo a agricultura uma grande contribuinte para a emissão do mesmo no Brasil. Para melhor modelar a perda de carbono do solo via CO2, deve-se considerar a variação espacial dessa variável, bem como dos atributos do solo, atento ao uso do solo agrícola e manejo. O presente estudo objetivou caracterizar a anisotropia espacial de FCO2 e atributos físicos e químicos do solo por meio da dimensão fractal (DF), na região do Cerrado no Mato Grosso do Sul. Para o estudo da anisotropia e geração de mapas de padrões espaciais foi utilizado uma malha regular amostral constituída de 102 pontos nas duas áreas. Para a FCO2 foram observados valores de DF 2,51 ± 0,41 para cana-de-açúcar e 2,61 ± 0,18 para eucalipto. A DF de FCO2 e dos atributos do solo estudadas por meio do gráfico de rosas mostrou que o fluxo de CO2 do solo apresenta variação espacial associada a diferentes atributos químicos e físicos do solo. Foram observados ganhos de precisão quando comparados os mapas de padrões espaciais isotrópico e anisotrópico para as variáveis FCO2, matéria orgânica do solo (MO) e a densidade do solo (Ds) nas duas áreas, indicados pela validação cruzada, com os valores de coeficiente de determinação entre 0,82 e 0,99 para área de cana-de-açúcar e 0,94 e 0,98 para áreas de eucalipto. FCO2 é um fenômeno de natureza complexa, sendo sua anisotropia espacial associada às variações espaciais dos demais atributos do solo e suas relações interespecíficas aliadas inclusive às ações antrópicas.

Carbon dioxide (CO2) is one of principal greenhouse gases, being the agriculture one of the contributor major to emission specially in Brazil. To better understands this phenomenon, it is necessary to consider the spatial variation of this variable, as well as the attributes of the soil, considering the type of agricultural land use and management. The present study objective of characterizing the spatial anisotropy of FCO2 and other soil physical and chemical attributes, through the fractal dimension (DF), in Cerrado region, Mato Grosso do Sul. For the study of anisotropy and maps generation of spatial patterns, a regular sample consisting of 102 points in both areas was used. To FCO2 anisotropy values of DF were observed for 2.51 ± 0.41 for sugarcane and 2.61 ± 0.18 for eucalyptus areas. DF of FCO2 and other soil attributes studied through the rose graphics showed that the FCO2 presents spatial variation associated with different soil chemical and physical attributes. Precision and accuracy gains were observed when comparing spatial patterns generated from isotropic and anisotropic modeling for FCO2, soil organic matter (MO) and soil density (Ds) in the two study areas, as indicated by cross-validation, with values of determination coefficient varying between 0.82 and 0.99 for sugarcane and 0.94 and 0.98 for eucalyptus areas. The spatial pattern indicated that the spatial variability of FCO2, soil organic matter (MO) and soil density (Ds) that obtained gains in the two studied areas with cross validation. The FCO2 is a phenomenon of complex nature being its spatial anisotropy related to the spatial variation of the other soil attributes and its intrinsically relationship in addition with the anthropogenic action in the different cultivated areas studied.
Anisotropy of spatial variability of co2 soil emission in a sugarcane and eucalyptus area
Keywords: Respiração do solo; Atributos do solo; Dependência espacial; Dimensão fractal; Soil respiration; Soil attributes; Spatial dependency; Fractal dimension